2020
DOI: 10.3390/aerospace7090129
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Maintenance Contributions to Commercial Air Transport Accidents

Abstract: Aircraft maintenance includes all the tasks needed to ensure an aircraft’s continuing airworthiness. Accidents that result from these maintenance activities can be used to assess safety. This research seeks to undertake a preliminary investigation of accidents that have maintenance contributions. An exploratory design was utilized, which commenced with a content analysis of the accidents with maintenance contributions (n = 35) in the official ICAO accident data set (N = 1277), followed by a quantitative ex-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Relative to the year, the point of even odds for fatalness was in 1983. Furthermore, the analysis unexpectantly revealed that fatigue accidents were more common in the early to mid-life of an aircraft, peaking in the 10 to 15-year-old age range and decreasing significantly beyond the age of 20 years; this was statistically significantly different to previous research looking at maintenance accidents previously reported (Khan et al, 2020), highlighting that fatigue failure occurs at younger airframe ages then maintenance accidents. There was no relationship observed between fatalness and the age of the aircraft for fatigue failure accident.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Relative to the year, the point of even odds for fatalness was in 1983. Furthermore, the analysis unexpectantly revealed that fatigue accidents were more common in the early to mid-life of an aircraft, peaking in the 10 to 15-year-old age range and decreasing significantly beyond the age of 20 years; this was statistically significantly different to previous research looking at maintenance accidents previously reported (Khan et al, 2020), highlighting that fatigue failure occurs at younger airframe ages then maintenance accidents. There was no relationship observed between fatalness and the age of the aircraft for fatigue failure accident.…”
Section: Discussioncontrasting
confidence: 86%
“…It should be noted, that as expected, the distribution of accidents follows more of a Poisson distribution, with the peak in the 10 to 15 years old range. If this distribution is compared with the similar distribution for maintenance related accidents (Khan et al, 2020), there are significantly more fatigue accidents that occur at less than 10 years of age, and significantly less for 10 to 30 years of age, when looking in age groups of 10 years, up to 50 ( 2 = 64, v = 4, p < 0.01). This indicates that contrary to the initial hypothesis, fatigue failures are more likely to occur with an aging airframe.…”
Section: Age Countmentioning
confidence: 88%
See 1 more Smart Citation
“…Used during maintenance tasks, these documents play a critical role in aviation safety and effectiveness. Errors that occur during the use of documents and following procedures can lead to consequences such as accidents and incidents (Hobbs, 2008; Khan et al , 2020; Insley and Turkoglu, 2021). The Aircraft Maintenance Manual (AMM) examined in this study is a manufacturer’s document and includes basic information about maintenance tasks, warnings and notes and how to perform the maintenance task (Kinnison and Sidiqui, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue is focused on safety themes with implications on airworthiness management. It offers a diverse set of analyses on aircraft maintenance accidents [1][2][3][4], empirical and systematic investigations on important continuing airworthiness matters [5][6][7] and research studies on methodologies for risk and safety assessment in continuing and initial airworthiness [8][9][10]. Overall, this collection of papers is a valuable addition to the published literature, and I am confident that the readers of Aerospace will find that useful.…”
mentioning
confidence: 99%